2022
DOI: 10.3390/ijerph191710839
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Quit Intentions among Adult Smokers in South Korea: Findings from the 2020 ITC Korea Survey

Abstract: Background: South Korea has made substantial progress on tobacco control, but cigarette smoking prevalence is still high. Previous studies were conducted before the use of nicotine vaping products (NVPs) or heated tobacco products (HTPs) became popular. Thus, whether the concurrent use of NVPs or HTPs affects quit intentions among Korean smokers remains a question that needs to be explored. This study aims to identify predictors of quit intentions among cigarette-only smokers and concurrent users of cigarettes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…6 A previous study showed that while most smokers in Korea were willing to quit (66.4%), less than half of them (35.4%) were willing to quit within 6 months, and the willing-to-quit rate in men is lower than in other similar-income countries. 7 The understanding of traits that amplify the risk of relapse among heavy smokers, despite the advances in tobacco cessation programs, is indeed in its early stages. 8 Previous research has shed light on various factors that influence the likelihood of a smoker returning to tobacco use after attempting to quit and these factors encompass a wide range of emotional, psychological, and social dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A previous study showed that while most smokers in Korea were willing to quit (66.4%), less than half of them (35.4%) were willing to quit within 6 months, and the willing-to-quit rate in men is lower than in other similar-income countries. 7 The understanding of traits that amplify the risk of relapse among heavy smokers, despite the advances in tobacco cessation programs, is indeed in its early stages. 8 Previous research has shed light on various factors that influence the likelihood of a smoker returning to tobacco use after attempting to quit and these factors encompass a wide range of emotional, psychological, and social dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…6 A previous study showed that while most smokers in Korea were willing to quit (66.4%), less than half of them (35.4%) were willing to quit within 6 months, and the willing-to-quit rate in men is lower than in other similar-income countries. 7…”
Section: Introductionmentioning
confidence: 99%
“…Initial quitting intentions are challenging to rise due to complicated impacting factors, including individual demographic characteristics, smoking conditions, and social and cultural norms [5][6][7] . Smokingrelated conditions have also proved to affect quitting intentions, such as the heaviness and duration of smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the intention to quit is known to be significantly associated with the previous quitting attempts and their duration [ 8 , 15 , 16 ]. There are several explanations for the relationship between past attempts and future intention to quit.…”
Section: Introductionmentioning
confidence: 99%